Whose dead is to be grieved? a comparative approach to contemporary war literature - M. Alosman, M Ikbal (Penerbit Universiti Kebangsaan Malaysia, 2024)
This paper examines Ben Fountain’s Billy Lynn's Long Halftime Walk (2012) and Sinan Antoon’s The Corpse Washer (2013) in terms of their representations of Americans and Iraqis in the context of the 2003 Iraq War. It aims to investigate and compare the novels' approaches to the lives/deaths of Americans and Iraqis, drawing on Judith Butler's claim that people in the West conceive of and deal with the lives/deaths of these non-Westerners differently. The lives of Westerners are made the most valuable at the expense of the safety and security of those outside these geographies. The analysis is made in two paradigms: 'Western lives' and 'non-Western lives'. While Fountain's novel focuses primarily on American soldiers, who are presented as the ultimate victims of the war, Antoon's provides a counter-narrative that challenges Fountain's argument and provides Iraqi characters with extended narrative spaces to recount their grievances. In Fountain's work, American deaths are thoroughly mourned at the expense of Iraqi deaths. Antoon's narrative, on the other hand, mourns these ungrievable souls and reclaims their ignored value.